High mortality among hospitalized adult patients with COVID-19 pneumonia in Peru: A single centre retrospective cohort study - Guiliana Mas-Ubillus; Pedro J. Ortiz; Jorge Huaringa-Marcelo; Paola Sarzo-Miranda; Patricia Muñoz-Aguirre; Alejandra Diaz-Ramos; Kattia Arribasplata-Purizaca; Doris Mendoza; Juan Rojas-Poma; Cristian Marcelo-Ruiz; Pedro Ayala-Diaz; Edwin Hidalgo-Arroyo; et al. (PLoS ONE, 2022)
Background Peru is the country with the world’s highest COVID-19 death rate per capita. Characteristics associated with increased mortality among adult patients with COVID-19 pneumonia in this setting are not well described. Methods Retrospective, single-center cohort study including 1537 adult patients hospitalized with a diagnosis of SARS-CoV-2 pneumonia between May 2020 and August 2020 at a national hospital in Lima, Peru. The primary outcome measure was in-hospital mortality. Results In-hospital mortality was 49.71%. The mean age was 60 ± 14.25 years, and 68.38% were males. We found an association between mortality and inflammatory markers, mainly leukocytes, D-dimer, lactate dehydrogenase, C-reactive protein and ferritin. A multivariate model adjusted for age, hypertension, diabetes mellitus, and corticosteroid use demonstrated that in-hospital mortality was associated with greater age (RR: 2.01, 95%CI: 1.59–2.52) and a higher level of oxygen requirement (RR: 2.77, 95%CI: 2.13–3.62). Conclusions: In-hospital mortality among COVID-19 patients in Peru is high and is associated with greater age and higher oxygen requirements.